Biological and functional evaluation of a novel pyrolytic carbon implant for the treatment of focal osteochondral defects in the medial femoral condyle: assessment in a canine model. Issue 1 (December 2016) - Salkeld, Samantha; Patron, Laura; Lien, Joan; Cook, Stephen; Jones, Deryk
Abstract Background Osteochondral defects continue to be a clinical treatment challenge, and when left untreated, may cause pain and functional impairment. Pyrolytic carbon is a unique isotropic biomaterial used in heart valve and small joint replacements due to its excellent wear properties and biocompatibility with bone and articular cartilage. Therefore, a proposed solution is to utilize a focal pyrolytic carbon hemiarthroplasty implant as an alternative resurfacing treatment strategy for isolated cartilage lesions. Methods A canine model (n = 9) was used to evaluate the in vivo histologic response and function of a pyrolytic carbon implant replacing a full-thickness osteochondral defect in the medial femoral condyle (MFC) of the knee. The gross appearance and histologic results were compared to an identical cobalt-chromium (Co-Cr) alloy implant placed in a defect in the contralateral MFC and evaluated up to 52 weeks. Results Extensive bone incorporation to the stem portion was observed for both implant types. The total mean histologic score for the cartilage of the MFC surrounding the pyrolytic carbon implants was significantly improved compared to that of the Co-Cr alloy implants at all evaluation periods (p < 0.05). Histologic grading and gross observations at 52 weeks for pyrolytic carbon implants were similar to those of Co-Cr alloy implants at 24 weeks. At 24 weeks, the mean total histologic score for Co-Cr alloy implants was 11.6 ± 0.7 (0–16 range point; 16 = normal appearance), while at 52 weeks, the mean total score for the pyrolytic carbon implants was 11.7 ± 1.3. Mean total histologic score of opposing medial tibia cartilage for the pyrolytic carbon implants was superior to that of the Co-Cr alloy group at all evaluation periods and significantly improved over the Co-Cr alloy implant group at 24 weeks (p = 0.001) and 52 weeks (p < 0.001). Conclusions Use of a pyrolytic carbon implant for reconstruction of a focal cartilage defect demonstrated effective implant fixation and superior in vivo response compared to an identical Co-Cr alloy implant.